MEMAHAMI SIFAT ADIKODRATI RAHMAT BAGI HIDUP KONKRET SECARA ANTROPOLOGI KRISTIANI LEGITIMATE AUTHORITY, RIGHT INTENTION, AND LAST RESORT FOR THE MORALITY OF HUMANITARIAN INTERVENTION IN POPE JOHN PAUL II’S MESSAGE FOR THE CELEBRATION OF THE WORLD DAY OF PEACE: “PEACE ON EARTH TO THOSE WHOM GOD LOVES” OF JANUARY 1, 2000 - Madalena Marseli (Jurnal Filsafat dan Teologi Katolik, 2022)
Humanitarian intervention is much debated topic in war and peace in the fields of moral, law, politic, philosophy in the international world. Entering the third millennium, in the context of struggle for universal peace, Pope John Paul II teached the morality of humanitarian intervention in the document Message for the Celebration of the World Day of Peace: “Peace on Earth to Those Whom God Loves” of January 1, 2000. This simple article tries to discuss, for understanding further, three demanding moral criteria for humanitarian intervention in this document, i.e.: legitimate authority, right intention, and last resort.